Opposing effects of acute versus chronic inhibition of p53 on decitabine’s efficacy in myeloid neoplasms - Tamura, Moe (Sci Rep, 2019)
Decitabine is a DNA methyltransferase inhibitor and is considered a promising drug to treat myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) with p53 mutations. However, whether loss of p53 in fact increases the response of MDS/AML cells to decitabine remains unclear. In this study, we assessed the role of p53 in MDS and AML cells treated with decitabine using mouse models for MLL-AF9-driven AML and mutant ASXL1-driven MDS/AML. CRISPR/Cas9-mediated depletion of p53 in MDS/AML cells did not increase, but rather decreased their sensitivity to decitabine. Forced expression of a dominant-negative p53 fragment (p53DD) in these cells also decreased their responses to decitabine, confirming that acute inhibition of p53 conferred resistance to decitabine in AML and MDS/AML cells. In contrast, MLL-AF9-expressing AML cells generated from bone marrow progenitors of Trp53-deficient mice were more sensitive to decitabine in vivo than their wild-type counterparts, suggesting that long-term chronic p53 deficiency increases decitabine sensitivity in AML cells. Taken together, these data revealed a multifaceted role for p53 to regulate responses of myeloid neoplasms to decitabine treatment.